PENGARUH TANAMAN HERBAL TERHADAP PENINGKATAN KADAR TROMBOSIT PADA ANAK DEMAM BERDARAH DENGUE (DBD) - Rina Sumartini (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Dengue hemorrhagic fever is a disease caused by the dengue virus where the virus has 4 variations, namely DEN-1, DEN-2, DEN-3, DEN-4. Dengue virus infection is mediated by a vector in the form of the Aedes aegypti mosquito which is widely spread throughout tropical areas, one of which is Indonesia. Independent actions that can be taken during home treatment using herbal plants. This literature review aims to determine the effect of herbal plants on increasing platelet levels in children. Qualitative research with a literature review approach with a search method using an electronic data base. The inclusion criteria used were using an intervention journal to overcome the problem of dengue fever using herbal remedies that can be accessed in full text. Based on a literature review in 4 journals, namely herbal plant therapy, namely the administration of Angkak, guava juice, date palm juice, and boiled papaya leaves, as an effort to increase platelet levels in dengue fever patients. The approach used is to collect and analyze research articles regarding herbal plants on increasing platelet levels in children. Articles were collected through the electronic database EBSCO and Google Schoolar using the keywords: herbal plants, dengue fever, platelets and children. The criteria for articles used are those published in the period between 2011-2022.